EDUCATIONAL PHILOSOPHY OF RABINDARNATH TAGORE WITH SPECIAL REFERENCE TO INTEGRAL EDUCATION - Zahida Jan (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Rabindranath Tagore, a luminary in literature, art, and philosophy, revolutionized education with his holistic and integral approach. His educational philosophy emphasized the development of the entire personality, integrating intellectual, physical, emotional, and spiritual growth. Rejecting the rigid and oppressive colonial education system, Tagore envisioned an education that fostered creativity, freedom, and a deep connection with nature. This vision materialized in Shantiniketan, a school he founded in 1901, which later evolved into the Visva-Bharati University. Shantiniketan embodied Tagore's principles through its open-air classrooms, diverse curriculum, and integration of arts and culture, fostering a sense of community and collaborative learning. Tagore's ideas have had a lasting impact; influencing progressive educational practices in India and globally, emphasizing experiential learning, arts integration, and global citizenship. Despite criticisms regarding the practicality of his methods in contemporary systems focused on standardization, Tagore's emphasis on environmental harmony, emotional well-being, creativity, and cultural understanding remains profoundly relevant. His visionary approach offers valuable insights for creating more humane and enriching educational experiences, highlighting the transformative potential of holistic and integrative education.